KELAYAKAN FINANSIAL UNIT USAHA JASA SEWA POMPA AIR UNTUK IRIGASI AIR PERMUKAAN DI DESA MEKAR MULYA KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Deby Februan Triwijaya; Wan Abbas Zakaria; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze the financial benefit of water pump rental services business unit and sensitivity of water pump rental services business unit.  This research uses  case study method in Mekar Mulya Village, Palas Sub-District, South Lampung Regency. The research location is intentionally chosen by consideration of the place is the central of rice production and there is surface water irrigation of paddy by utilizing water pump. The number of respondent is 34 people taken by sensus method. Data of this research is collected on November 2015 – January 2016. The analysis data uses quantitative and qualitative descriptive analysis.  The result of this research show pump irrigation feasible and profitable to be developed. NPV of 329,864,982.14, IRR of 76.95 percent, Gross B/C ratio of 1.3, Net B/C Ratio of 5.39 and payback period (PP) of 2.39. Water pump rental services business unit sensitive to changes in fuel cost increase of 66.67 percent and oil cost increase of 17.86 percent.  Key words: financial feasible, pump irrigation, rice farm